The basis for germline specificity of the hobo transposable element in Drosophila melanogaster. - Calvi, B R (EMBO J, 1994)
Previous results suggested that the hobo transposable element is active predominantly in the germline of Drosophila. We investigate germline restriction of hobo transposition by testing in vitro modified elements for their ability to mobilize marked elements in vivo. Although intact hobo elements are germline specific, an hsp70 promoter-hobo transposase fusion is active in the soma. Analysis of the hsp70-promoted transcript does not provide evidence for splicing. Moreover, the hobo promoter confers germline bias to a highly sensitive reporter, delta 2-3 P transposase. These results indicate that hobo transposition is germline specific due to regulation of transposase production at the level of transcription. Thus, although hobo is similar to the P transposable element in organization and tissue specificity, it differs in the underlying mechanism governing germline specific activity. IMAGES: